Quantifying the dynamic evolution of organic, inorganic and biological synergistic fouling during nanofiltration using statistical approaches. (December 2019) - Lin, Weichen; Li, Mengchen; Wang, Yunhong; Wang, Xiaomao; Xue, Kai; Xiao, Kang; Huang, Xia
Graphical abstract: Highlights: The interactive roles of organic, inorganic and biological fouling were quantified. Organic-inorganic, organic-bio and organic-inorganic-bio synergies were prominent. Organics can also cause fouling individually but inorganic and biofoulants cannot. Fouling was delineated into three stages by statistical analysis of foulant features. Fouling control may be targeted more accurately on foulant type or fouling stage. Abstract: The dynamic process of membrane fouling was characterized during relatively long-term (30 d) continuous nanofiltration (NF) of a real wastewater secondary effluent, with the roles of organic, inorganic and biological foulants quantified via statistical analyses. The analyses were based on time-series data of physical properties (morphology, roughness, hydrophilicity and charge), chemical compositions (X-ray and infrared responses) and biomass (adenosine triphosphate, ATP) on the membrane surface during fouling evolution. The individual and interactive contributions of organic factor (typical functional groups), inorganic factor (Ca as a representative) and biological factor (ATP amount) to fouling were quantified via multiple linear regression coupled with variance partitioning analysis. About 78% of the variance of filtration resistance can be explained by these factors, among which 16% was contributed by individual effect of organics (via e.g. physical adsorption), 21% by organic-inorganic binary effect (in the form of e.g. Ca-complex), 13% by organic-biological binary effect (organics as the nutrient/product of microorganisms), and 24% by organic-inorganic-biological ternary interaction. Organic matter was universally involved in these effects. The interrelations among fouling factors, foulant layer properties and filtration time were comprehensively explored via redundancy analysis, which clearly delineated the fouling evolution into three major stages: Stage I (0–1 d) for initial fouling mainly due to rapid organic adsorption; Stage II (1–10 d) mainly for the gradual growth of Ca-organic combined fouling; and Stage III (10–30 d) for the eventual maturation of biofouling. These may provide foundations for a targeted fouling control based on foulant type or fouling stage.